A systematic review of the evidence of how hospitals capture financial benefits of process improvement and the impact on hospital financial performance - Jane Evans; Sandra G. Leggat; Danny Samson (BMC, 2023)
Abstract Background Governments, funders and hospital managers around the world are looking for ways to address the continual growth in expenditure by reducing the level of waste in the healthcare delivery system and improving the value of care provided to patients. Process improvement methods are applied to increase high value care, reduce low value care and remove waste from care processes. The purpose of this study is to review the literature to identify the methods used by hospitals to measure and capture financial benefits from PI initiatives to identify best practice. The review also pursues the way hospitals collate these benefits at the enterprise level to achieve improved financial performance. Methods A systematic review was undertaken in line with the PRISMA process and employed qualitative research methods. Databases searched were Medline, Cochrane Library, Cumulative Index to Nursing and Allied Health Literature (CINHAL), Web of Science and SCOPUS. The initial search was conducted in in July 2021 with a follow up search conducted in February 2023 using the same search terms and databases to identify additional studies published in the intervening period. The search terms were identified through the PICO (Participants, Interventions, Comparisons and Outcomes) method. Results Seven papers were identified that reported reduction in care process waste or improvement of the value of care using an evidence-based PI approach and included financial benefits analysis. Positive financial impact was measured for the PI initiatives but none of the studies reported how these financial benefits were captured or applied at the enterprise level. Three of the studies suggested that sophisticated cost accounting systems were required to enable this. Conclusion The study demonstrates the paucity of literature in the field of PI and financial benefits measurement in healthcare. Where financial benefits are documented, they vary in terms of cost inclusions and the 'level' at which the costs were measured. Further research on best practice financial measurement methods is needed to enable other hospitals to measure and capture financial benefits arising from their PI programs.